2020
DOI: 10.3928/1081597x-20200212-02
|View full text |Cite
|
Sign up to set email alerts
|

Spherical Aberration Customization to Extend the Depth of Focus With a Clinical Adaptive Optics Visual Simulator

Abstract: PURPOSE: To evaluate the use of the VAO adaptive optics visual simulator (Voptica SL, Murcia, Spain) for customization of spherical aberration to increase depth of focus. METHODS: Through-focus visual acuity with both high- and low-contrast letters from +1.00 to −3.00 diopters (D) was measured in 17 dilated eyes with three different induced amounts of spherical aberration for a 4.5-mm pupil diameter: control (0 µm), −0.15 µm, and −0.30 µm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 38 publications
0
23
1
Order By: Relevance
“…Zhang et al demonstrated that ( 33 ) an aspheric IOL with a low negative or zero primary spherical aberration is recommended for cataract patients with high myopia. Hervella et al ( 34 ) found that negative values of spherical aberration extend the depth of focus in different ways depending on each patient. Tzamalis et al ( 35 ) revealed that Bioline yellow IOL indicated lower contrast sensitivity under mesopic conditions when glare was applied but resulted in less trefoil aberrations after uneventful cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al demonstrated that ( 33 ) an aspheric IOL with a low negative or zero primary spherical aberration is recommended for cataract patients with high myopia. Hervella et al ( 34 ) found that negative values of spherical aberration extend the depth of focus in different ways depending on each patient. Tzamalis et al ( 35 ) revealed that Bioline yellow IOL indicated lower contrast sensitivity under mesopic conditions when glare was applied but resulted in less trefoil aberrations after uneventful cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4(A) shows a schematic diagram of the binocular version of the AO visual simulator. New capabilities of the AOVS, include extended defocus range of operation with the addition of tunable lenses [ 67 ] and we have contributed to the transition to a commercial clinical apparatus developed by Voptica SL, the VAO [ 68 ]. Beyond the correction of aberrations, intraocular scatter affects the eye’s image quality, with special severity in cataracts.…”
Section: Murcia University (Loum) Adaptive Optics Visual Simulatorsmentioning
confidence: 99%
“…The experimental measurements in this work were taken using the VAO adaptive optics visual simulator (Voptica S.L., Murcia, Spain). This clinical instrument allows to place optical stimuli different vergences through a micro display and to show to the patient its image through any optical phase profile [35,36]. The stimulus was an optotype with three high-contrast letters (tumbling Es) of different sizes corresponding to visual acuities of 0.4; 0.2 and 0.0 logMAR units.…”
Section: Adaptive Optics Visual Simulatormentioning
confidence: 99%